A STUDY ON THE EFFECTIVENESS OF CROSSWORD PUZZLE AS COMPARED TO CONVENTIONAL METHOD IN TEACHING VOCABULARY - Panjaitan, Nelson B.; Simbolon, Erwin; Hendriks, Anne Lou (Journal of Language Pedagogy, 2011)
This study is entitled âThe Effectiveness of Crossword Puzzle as Compared The Conventional Method in Teaching Vocabulary.â The research was administered to answer the question âIs crossword puzzle as compared to other methods effective in improving student vocabulary achievement?â The data were collected through pretest and posttest, administered to 35 student and the data was analyzed by using T-test. The participants of this study were the grade five elementary pupils of kartika elementary school. in section 5A there were 34 pupils who wereÂ  taught using conventional method and section 5B there were 35 pupils who were taught using crossword puzzle method. The age of the participants were between 11-15 years old. From the computation of the pretest and posttest, the result mean of pretest control group=51.17, the result mean of pretest experimental group=55.14. and the mean posttest control group= 56.61,the mean posttest experiment group= 63.42. The result shows that t counted =2.106>t table = 1,684. There is significant different crossword puzzle method effective to improve vocabulary skills. The researcher hopes that the finding of present crossword puzzle method could give some contribution to the improvement vocabulary especially for the students of Kartika X-3, Parompong, Bandung.